Assessment reform in education policy and practice - Berry, Rita; Adamson, Bob (Education in the Asia-Pacific region: issues, concerns and prospects, 2011)
The early 21st century saw education reforms in many countries that were driven by new economic imperatives and that generally called for a realignment of assessment concepts to match the prevailing educational goals. Divided into two sections and fourteen chapters, this book provides an interpretation of why current assessment policies take the form that they do and the role and status of assessment for learning in the policy-making debates, and identifies the problems and challenges that have occurred and the resolutions that might be proposed. The chapters in the first section, assessment reform experiences, review the history and development of assessment policy and practice in different countries around the world and focus on the issues related to assessment reform in these countries. The salient features of the issues identified are discussed in the second section, issues in the spotlight, of the book. The chapters in this section analyze the origins/causes and discuss complexities, tensions, dilemmas and/or possibilities associated with the issue as well as setting out the implications of the issue for the future of assessment reform, and possible ways forward.